Penggunaan Tanda Untuk Berdakwah Pada Akun Instagram Punk Muslim - Naufal Aulia Fiermeiza; Luthfi, Muhammad Farisan (Sehati Abdimas, 2024)
Instagram is a part of social media that is used to share photos and videos, both individually and in groups. With the existence of Instagram, this is utilized by the Muslim Punk community for preaching. Punk is one of the subcultures that exist in the world. As subcultural movements always voice their group's journey to society. As seen in the Muslim Punk community that synergizes and operates through the Instagram account @punkmuslim, with a goal that is no longer purely punk but punk that acknowledges their religious identity. (Islam). Instagram has become a platform for preaching for this community. The use of signs within this community has turned Instagram into a field for preaching, a space for discussion, and a place for creation for this Muslim punk community. We can see that punks, who are based on the principles of anti-establishment and rejection of submission, are actually active on social media and submit and adhere to the teachings of Islam. The purpose of this research is to interpret the signs used and played on the Instagram accounts of Muslim Punks. These signs are used by this community to preach to their followers who are not yet familiar with Islam. The method used by the author in this research is the visual analysis method. The elaboration of every existing visual form, which the author then relates to signs. This research uses observational studies on Instagram accounts. The results of this research are descriptions and interpretations of the signs used and played by the Muslim punk community for preaching.